A Multivariate Generalizability Theory Approach to College Students' Evaluation of Teaching - Li, Guangming; Hou, Guiyun; Wang, Xingjun; Yang, Dong; Jian, Hu; Wang, Weijun (Frontiers in Psychology, 2018)
Teachers' teaching level evaluation is an important component in classroom teaching and professional promotion in the institutions of higher learning in China. Many self-made questionnaires are currently being administered to Chinese college students in evaluating their teachers’ class performance. Quite often, due to the absence of strong educational and psychological measurements and theoretical foundations for these questionnaires, their dependability is open to doubt. Evaluation time points, the number of students, major type, and curriculum type were examined in relation to college students’ perceptions on their teachers’ classroom teaching performance, using Teachers’ Teaching Level Evaluation Scale for Colleges (TTLES-C). Data were collected in a sample of 556 students at two time points from three Chinese universities and were analyzed using multivariate generalizability theory (GT). Results showed that evaluations at the beginning of the spring semester produced better outcomes than did evaluations at the end of the fall semester, and twenty student evaluators were sufficient to ensure good dependability. Results also revealed that the evaluation dependability of science curriculum appeared higher than that of liberal arts curriculum. Recommendations were discussed on the evaluation criteria and mode.